4‐Oxo‐4, 5, 6, 7‐tetrahydro‐1H‐pyrazolo[3, 4‐d]pyrimidine Derivatives: Design, Synthesis, Insecticidal Assay and Binding Mode Studies. Issue 8 (14th July 2022) - Li, Guanglong; Xiao, Keya; Shi, Man; Shuai, Jing; Xu, Zhiping; Li, Zhong; Cheng, Jiagao
Abstract: A series of 4‐oxo‐4, 5, 6, 7‐tetrahydro‐1 H ‐pyrazolo[3, 4‐ d ]pyrimidine derivatives were designed and synthesized based on the fipronil low energy conformation by scaffold hopping strategy. Physicochemical properties calculation, insecticidal assay and binding mode studies were also performed. It was found that the target compounds displayed lower insecticidal activities than fipronil. The differences in binding modes between these compounds and fipronil may be the major reason for reduced insecticidal activities. Abstract :